Adventures in the Irreal: Science Fiction, Utopia and Contemporary Art Practice - Broadhurst, Kieron (Curtin University, 2020)
Adventures in the Irreal is a practice-led investigation which explores the speculative possibilities of science fiction from within a contemporary art practice. As part of this process two methods for creating science fiction artworks are developed. These methods are then utilised in the creation of three science fiction artworks, with each artwork offering a unique, speculative approach to utopian aspects of its real world subject matter.